Togo : Second Review Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses Togo's Second Review Under the Extended Credit Facility (ECF) and Request for Modification of Performance Criteria. Despite the ensuing revenue underperformance, the fiscal position improved significantly as expenditure was curtailed. All continuous and end-December 2017 quantitative performance criteria (QPCs) were met, as well as the structural benchmarks. The indicative target on fiscal revenue was missed by about 2 percent of GDP and the indicative target on social spending was missed by a small margin (0.2 percent of GDP). The IMF staff supports the completion of the second ECF review as well as the modification of end-June 2018 QPCs on the domestic primary balance and net domestic financing and the continuous QPC on nonconcessional external borrowing.